2003
DOI: 10.1051/0004-6361:20031342
|View full text |Cite
|
Sign up to set email alerts
|

Rotation, pulsations and magnetic field in V 2052 Ophiuchi: A new He-strong star

Abstract: Abstract. V 2052 Oph is a β Cep star with v sin i ∼ 60 km s −1 . The behavior of its stellar wind was studied in the ultraviolet wavelength region with the IUE satellite. It revealed periodic variations in the equivalent widths (EW) of the resonance lines of wind-sensitive ions with a period of 3.638833 d, which is identified as the rotational period. These variations are typical of magnetic stars. Therefore time-resolved circular spectropolarimetric observations were obtained with the Musicoséchelle spectropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 37 publications
3
92
0
1
Order By: Relevance
“…For all these stars we have magnetic field detections. In addition, two other β Cephei stars, V2052 Oph and β Cep, of their sample with detected longitudinal magnetic fields of the order of ∼100 G (Neiner et al 2003b;Henrichs et al 2000) were found to show nitrogen enhancement. For the sixth β Cephei star with a detected magnetic field, HD 180642, Morel & Aerts (2007) found a mild nitrogen overabundance, though boron data are not available.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For all these stars we have magnetic field detections. In addition, two other β Cephei stars, V2052 Oph and β Cep, of their sample with detected longitudinal magnetic fields of the order of ∼100 G (Neiner et al 2003b;Henrichs et al 2000) were found to show nitrogen enhancement. For the sixth β Cephei star with a detected magnetic field, HD 180642, Morel & Aerts (2007) found a mild nitrogen overabundance, though boron data are not available.…”
Section: Resultsmentioning
confidence: 94%
“…The first detection of a weak magnetic field in the SPB star ζ Cas was reported by Neiner et al (2003b). In our first publication on the magnetic survey of pulsating B-type stars (Hubrig et al 2006), we announced detections of weak mean longitudinal magnetic fields of the order of a few hundred Gauss in 13 SPB stars and in the β Cephei star ξ 1 CMa.…”
Section: Introductionmentioning
confidence: 95%
“…A magnetic field was reported in the β Cep star V2052 Oph = HD 163472 by Neiner et al (2003b), again based on MuSiCoS observations. The measurements presented appear to support the claimed discovery, but are very close to the limit of detection.…”
Section: β Cephei Pulsators and Slowly Pulsating B Starsmentioning
confidence: 80%
“…A preliminary analysis of the star indicated inconsistencies of the solution, which were unexpected in view of the "normal" appearance implied by the analysis of Morel et al (2006). However, a detailed study by Neiner et al (2003) found HD 163472 to be chemically peculiar, in particular it is a He-strong star. Diffusion in the magnetic atmosphere renders this otherwise highly interesting star useless for our purpose.…”
Section: Stars Excluded From the Analysismentioning
confidence: 94%
“…Systematic effects on the abundance analysis due to the presence of magnetic fields are also not expected. Only three sample stars have a confirmed magnetic field, β Cep (Henrichs et al 2000), ζ Cas (Neiner et al 2003) and τ Sco (Donati et al 2006). To date, none of these shows observational evidence for abundance spots or vertical chemical stratification.…”
Section: Chemical Abundancesmentioning
confidence: 95%